Informal care provision and work disability days - Christiane Roller; Magdalena A. Stroka-Wetsch; Roland Linder (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2016)
Due to the demographic change and the concomitant ageing of society, the labor force will reduce in Germany in the following decades. Simultaneously, the demand for informal care will increase as a result of the ageing society. Informal care is assumed being the least expensive form of care and is the most common form of care in Germany. However, the literature conveys the impression that informal care is not easily compatible with a range of situations in life. This is especially confirmed by findings of negative health effects of informal caregiving. Based on these findings, it could be suspected that there have to be large effects on employment, as individuals with health restrictions are supposed to work less. Indeed, findings on effects of informal care provision on employment indicate a rather small or even an insignificant effect. We think that health problems become manifest in some form or another. Thus, the effects of informal care provision on labor supply are possibly larger than it has been assumed so far. To verify our hypothesis, we examine the effects of informal caregiving on a health related labormarket outcome in the form of work disability days using administrative data of Germany's largest sickness fund, the Techniker Krankenkasse with more than 5 million observations. In order to identify the effects of informal care on work disability days, linear regression models are estimated in which is controlled for timeinvariant heterogeneity. The results illustrate a significant positive relationship between informal caregiving and the number of work disability days. – – Während als eindeutig belegt gilt, dass die informelle Pflege durch Angehörige die in Deutschland am weitesten verbreitete Pflegeform darstellt, besteht in der Literatur kein Konsens über die Auswirkungen der Erbringung derartiger Pflegeleistungen auf die Arbeitsmarktpartizipation und Gesundheit. Die Ergebnisse bereits vorhandener Studien weisen zwar überwiegend auf negative Effekte der Pflege auf die Gesundheit hin, dies spiegelt sich jedoch nicht in einer entsprechenden Verringerung des Arbeitsangebotes wider. Ziel dieser Studie ist es daher zu untersuchen, inwiefern es eine indirekte Verringerung des Arbeitsangebotes gibt, die aus der gesundheitlichen Belastung durch die Pflege resultiert und sich womöglich auf Arbeitsunfähigkeitstage auswirkt. Hierzu werden Routinedaten Deutschlands größter Krankenkasse (der Techniker Krankenkasse) mit über 10 Millionen Versicherten ausgewertet. Die Ergebnisse zeigen große Effekte der informellen Pflegeerbringung auf die Arbeitsunfähigkeitstage, was darauf hinweist, dass die Arbeitsmarkteffekte ohne die Betrachtung der Arbeitsunfähigkeitstage in der bisher existierenden Literatur unterschätzt wurden.
Keywords: I10; J10; 330; informal care; work disability days; demographic change; ageing society; administrative data; fixed-effects